A Standardized Investigational Ki-67 Immunohistochemistry Assay Used to Assess High-Risk Early Breast Cancer Patients in the monarchE Phase 3 Clinical Study Identifies a Population With Greater Risk of Disease Recurrence When Treated With Endocrine Therapy Alone. Issue 4 (25th April 2022) - Polewski, Monika D.; Nielsen, Gitte B.; Gu, Ying; Weaver, Aaron T.; Gegg, Gavin; Tabuena-Frolli, Siena; Cajaiba, Mariana; Hanks, Debra; Method, Michael; Press, Michael F.; Gottstein, Claudia; Gruver, Aaron M.
Abstract : The objectives were to develop a standardized Ki-67 immunohistochemistry (IHC) method for precise, robust, and reproducible assessment of patients with early breast cancer, and utilize this assay to evaluate patients participating in the monarchE study (NCT03155997). The Ki-67 assay was developed and validated for sensitivity, specificity, repeatability, precision, and robustness using a predefined ≥20% cutoff. Reproducibility studies (intersite and intrasite, interobserver and intraobserver) were conducted at 3 external laboratories using detailed scoring instructions designed for monarchE. Using the assay, patient tumors were classified as displaying high (≥20%) or low (<20%) Ki-67 expression; Kaplan-Meier methods evaluated 2-year invasive disease-free survival rates for these 2 groups among patients treated with endocrine therapy (ET) alone. All analytical validation and reproducibility studies achieved point estimates of >90% for negative, positive, and overall percent agreement. Intersite reproducibility produced point estimate values of 94.7%, 100.0%, and 97.3%. External interobserver reproducibility produced point estimate values of 98.9%, 97.8%, and 98.3%. Among 1954 patients receiving ET alone, 986 (50.5%) had high and 968 (49.5%) had low Ki-67 expression. Patients with high Ki-67 had a clinically meaningful increased risk of developing invasive disease within 2 years compared with those with low Ki-67 [2-y invasive disease-free survival rate: 86.1% (95% confidence interval: 83.1%-88.7%) vs. 92.0% (95% confidence interval: 89.7%-93.9%), respectively]. This standardized Ki-67 methodology resulted in high concordance across multiple laboratories, and its use in the monarchE study prospectively demonstrated the prognostic value of Ki-67 IHC in HR+, HER2− early breast cancer with high-risk clinicopathologic features.